A unified thermo-elasto-viscoplastic model for soft rock. (March 2017) - Xiong, Yong-lin; Ye, Guan-lin; Zhu, He-hua; Zhang, Sheng; Zhang, Feng
Abstract: A unified advanced thermo-elasto-viscoplastic constitutive model for soft rock is proposed in the critical state framework. The model is able to describe the fundamental mechanical behavior of soft rock such as elastoplastic, strain hardening and softening, time dependency, confining stress dependency, intermediate principal stress dependency and temperature dependency with one set of parameters. The thermal-induced equivalent stress tensor σ ˜ i j and the transform stress tensor t ij are adopted to consider the influence of temperature and intermediate principal stress. Two evolution equations for the shear strength and the overconsolidation are newly introduced to take into consideration the influences of the confining stress and time dependent behavior, respectively. The capability of the model is carefully validated through a series of element tests of different soft rocks. The material parameters involved in the model have clear physical meanings and can be easily determined by the triaxial compression tests and creep tests. Highlights: Unified description of thermo-elasto-viscoplastic behavior of soft rock. Confining stress dependency of shear strength at critical state. Thermal-induced equivalent stress tensor. Validation by various laboratory tests.